Determination of primary resistance of Helicobacter pylori isolates to clarithromycin and amoxicilin by disc difussion method and the comparison with resistance in recurrent cases - Murat PALABIYIKOĞLU; Fikret ŞAHİN and Ali ÖZDEN and Özden UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2019)
-